2010
DOI: 10.1159/000320286
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Association between the Use of Anabolic-Androgenic Steroids and Criminality?

Abstract: Aims: The aim of this study was to improve our understanding of the proposed association between anabolic-androgenic steroids (AAS) and criminality. Methods: The study was based on interviews and criminality data involving 32 users of AAS who had sought treatment for AAS-related problems at a psychiatric addiction clinic in Sweden. A score derived from the number of crimes, their level of severity and the relevant time periods was computed to allow comparisons between subgroups sorted according to type and tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 74 publications
1
21
0
1
Order By: Relevance
“…Our results extend this work using a general population survey and indicate that many adolescents who use AAS are prone to engage in similar acts of aggression. Also noteworthy is the high proportion of poly-substance abuse among AAS users, a finding that has been reported previously [9,12,13,24] . Indeed, only 2 of the AAS users in our study had not used at least one other type of illicit drug -so that it was not feasible for us to adjust for other illicit drug use when performing analyses of the AAS-user group in this study.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our results extend this work using a general population survey and indicate that many adolescents who use AAS are prone to engage in similar acts of aggression. Also noteworthy is the high proportion of poly-substance abuse among AAS users, a finding that has been reported previously [9,12,13,24] . Indeed, only 2 of the AAS users in our study had not used at least one other type of illicit drug -so that it was not feasible for us to adjust for other illicit drug use when performing analyses of the AAS-user group in this study.…”
Section: Discussionsupporting
confidence: 68%
“…In a general population survey of Swedish men aged 15-64 years, Hakansson et al [11] reported that AAS use was strongly associated with a lifetime history of illicit drug use and the misuse of prescription drugs. Similarly, in 2 related studies conducted in Sweden, Skårberg and colleagues found significant associations between AAS use, poly-substance dependence and serious criminality (violence and weapons offences) [12,13] . What remains unclear in the scientific literature is whether these antisocial behaviors are more common among AAS users compared with other non-AAS illicit drug users.…”
Section: Introductionmentioning
confidence: 80%
“…Thus, the present unweighted data cannot readily be used for estimations of prevalence, whereas in the present study, we have used the data for calculations of statistical associations. Another limitation is that while AAS use is known to be related to criminal behavior [29], the present survey did not contain a variable describing general criminal involvement. Thus, while several other known or potential risk factors could be studied also in this general population survey, criminal involvement was not one of those.…”
Section: Limitationsmentioning
confidence: 99%
“…Other possible correlates of AAS use may be negative school experiences, lower level of education, a disadvantageous childhood, and a more unstable current social situation [28]. Also, a link between AAS use and criminal behavior has been described [29]. Intuitively, while the use of AAS appears to be more likely to occur in some risk groups and settings, it is relevant to examine individuals who have been offered to use AAS without actually using, and how users differ from these nonusers.…”
Section: Introductionmentioning
confidence: 99%
“…According to the criminals, the most concerning group, they are using AAS with the purpose to increase muscle mass, show a brutal exterior, increase self confidence and to be able to carry out a crime [2]. Use of AAS has been associated with heavy criminality especially violent crimes and one study also showed a higher risk of having been convicted of a crime involving weapon or fraud among individuals that had used AAS [3,4].…”
Section: Introductionmentioning
confidence: 99%